Isaac Newton’s Geometric Biblical Interpretation - LIU, Zhiqiang (Journal of Research for Christianity in China (JRCC), 2023)
The public usually focuses on Isaac Newton’s achievements in the field of science, but ignores his achievements in the field of religion. With the discovery of Newton’s manuscripts, his religious ideas began to be gradually revealed. This paper discusses Newton’s interpretation of the Book of Revelation and his geometric interpretation method of “rule - definition - proposition - proof – application”, trying to restore Newton’s pursuit of rational and geometric methods to understand nature and the Bible, and to return to true religion and  Prisca Sapientia.
Keywords: Newton’s manuscript, Biblical interpretation, Geometric interpretation